PARTISIPASI PEMUDA DALAM PENGELOLAAN HUTAN KEMASYARAKATAN DI DESA KAHAYYA KABUPATEN BULUKUMBA - Andi Atira Ilfa; Supratman Supratman; Muhammad Alif K.S (Jurnal Belantara, 2021)
This study aims to analyze the level of youth participation in community forest (HKm) management, analyze the driving forces and restraining forces of youth participation in community forest management and formulate strategies for increasing youth participation in community forest management. The data obtained were identified and reviewed in the form of a frequency table of Arnstein's degree of involvement, then analyzed descriptively by the Forces Field Analysis and Focus Group Discussion methods. The results showed the level of youth participation was at the degree of non-participation, with a percentage of 71.43%. The factors that encourage youth participation consist of the group facilitator, group meetings, work plan documents, assistance from various parties, the formation of the Social Forestry Business Group (KUPS), and the desire of youth to participate. The factors that inhibit youth participation consist of: lack of youth knowledge in managing community forest, not yet implementing work boundary arrangement activities, youth are not involved in the process of making work plans, and community forest implementation is still carried out individually, the farming experience is still lacking, lack of group capital makes the price of raw materials unstable. An appropriate strategy for increasing youth participation in the management of community forest consists of Conducting meetings involving facilitator, farmer groups and youth to discuss the implementation of management activities (planning, implementation & evaluation) of the community forest-conduct socialization and meetings regarding the contents of the community forest documents that have been made. Make internal group rules regarding product sales prices. Enhance the role of KUPS and conduct training for KUPS administrators to increase their capacity. Youth participate in various types of training conducted by government and non-government organizations (NGOs).